PENGARUH TINGKAT KESEHHATAN BANK TERHADAP PERTUMBUHAN LABA BERDASARKAN PENDEKATAN RISIKO (Studi pada Lembaga Keuangan Bank Badan Usaha Milik Negara yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2015) - Yunika, Ricka; Muslih, Muhamad (Aksara Public, 2018)
This study aims to investigate bank’s health levels by RBBR (Risk-Based Bank Rating) method, that is credit risk, market risk, capital adequacy, good corporate governance, profitability and liquidity risk and profit growth at Indonesian State-Owned Enterprises Banking period 2011-2015. The data used in this research is obtained from financial statement data.The sampling technique used is saturation sampling/census, then the sample was taken from the entire population consists of 4 Indonesian state-owned banks with research period in 2011-2015. Data analysis method in this research is panel data regression analysis by using software Eviews version 9. Based on the results of data processing, shows that credit risk variables (NPL), market risk (NOP), Capital (CAR), GCG, Rentability (NIM), and Liquidity Risk has significant simultaneously influence to profit growth in Indonesian State-Owned Enterprises Banking 2011-2015. The The partial influence of this research shows that credit risk (NPL) has significant negative effect,market risk (PDN) has significant negative effect, capital adequacy (CAR) has significant positive effect, good corporate governance has not significant effect, profitability (NIM) has not significant effect and liquidity risk has significant positive effect toward profit’s growth.